Peningkatan Kompetensi Guru Melalui Pengenalan dan Pelatihan Model Pembelajaran OIDDE di MTs-MA Ma'arif Bangil - Hanik Fitrotul Azizah; Atok Miftachul Hudha; Poncojari Wahyono; Nurwidodo Nurwidodo (Jurnal Ragam Pengabdian, 2026)
The development of 21st-century education requires teachers to develop critical thinking, creativity, communication, and collaboration in students, while the Independent Curriculum demands student-centered learning. Initial observations at MTs-MA Ma'arif Bangil showed that most teachers still apply teacher-centered learning, resulting in suboptimal student engagement, and their understanding of the OIDDE (Orientation, Identify, Discussion, Decision, Engage in Behavior) learning model remains limited. This community service activity aimed to improve teacher competency through the introduction and training of the OIDDE learning model. The workshop was conducted on May 9, 2026, involving 34 teachers. The material covered basic concepts, implementation stages, and the practice of developing learning tools based on the OIDDE model, presented by the model developer, Prof. Dr. Atok Miftachul Hudha, M.Pd. Evaluation used pre-tests, post-tests, and satisfaction questionnaires. The results showed an increase in the average score from 86.47 in the pre-test to 93.82 in the post-test, while participant satisfaction reached 92%, categorized as very good.